Several common variants modulate heart rate, PR interval and QRS duration - Holm, Hilma; Gudbjartsson, Daniel F; Arnar, David O; Thorleifsson, Gudmar; Thorgeirsson, Gudmundur; Stefansdottir, Hrafnhildur; Gudjonsson, Sigurjon A; Jonasdottir, Aslaug; Mathiesen, Ellisiv B; Njølstad, Inger; Nyrnes, Audhild; Wilsgaard, Tom; et al. (Nature genetics, 2010)
Hilma Holm and colleagues report genome-wide association studies to electrocardiographic measures of heart rate, PR interval, QRS duration and QT interval. Electrocardiographic measures are indicative of the function of the cardiac conduction system. To search for sequence variants that modulate heart rate, PR interval and QRS duration in individuals of European descent, we performed a genome-wide association study in ∼10,000 individuals and followed up the top signals in an additional ∼10,000 individuals. We identified several genome-wide significant associations (with P < 1.6 × 10 −7 ). We identified one locus for heart rate ( MYH6 ), four for PR interval ( TBX5 , SCN10A , CAV1 and ARHGAP24 ) and four for QRS duration ( TBX5 , SCN10A , 6p21 and 10q21). We tested for association between these loci and subjects with selected arrhythmias in Icelandic and Norwegian case-control sample sets. We observed correlations between TBX5 and CAV1 and atrial fibrillation ( P = 4.0 × 10 −5 and P = 0.00032, respectively), between TBX5 and advanced atrioventricular block ( P = 0.0067), and between SCN10A and pacemaker implantation ( P = 0.0029). We also replicated previously described associations with the QT interval.